Relationship between effect of tetrandrine on pleurisy and phospholipase A2 - He Hua-mei; Li Xin-fang; Zhang Min (Acta Pharmacologica Sinica, 2016)
A model of pleurisy was established with an intrapleural injection of carrageenan (Car, 10 mg.kg-1) in rats to explore the anti-inflammatory action of tetrandrine (Tet) and its mechanism. After the injection of Car, the exudate, protein and neutrophils appeared in the pleural cavity of rats at 2 h, then increased progressively, and reached a peak level at 12 h and remained high up to 48 h. The phospholipase A2(PLA2) activity of neutrophils (Neu-PLA2) and of the acellular component (ACC-PLA2) in the pleural exudate intensified at 2 h, rose to maximal intensity at 8 h, and started to decline at 48 h. The changes of the amount of exudate, protein content and neutrophil count, and parameters indicating the inflammatory response, were closely related to that of the PLA2 activity (r = 0.749-0.928, P < 0.05 or 0.01). By ig gavage of Tet (10-80 mg.kg-1) to rats at 30 min before and 4 h after the injection of Car, the inflammatory parameters were reduced and the PLA2 activity was inhibited, dose-dependently. The reductions of the inflammatory parameters were significantly associated with the inhibition of the PLA2 activity (r = 0.928-0.993, P < 0.05 or 0.01). These results indicate that Tet has a fine anti-inflammatory action and its mechanism may involve the inhibition on the activation and release of PLA2 of inflammatory cells.